Bioprinting of Small-Diameter Blood Vessels. (June 2021) - Cao, Xia; Maharjan, Sushila; Ashfaq, Ramla; Shin, Jane; Zhang, Yu Shrike
Abstract: There has been an increasing demand for bioengineered blood vessels for utilization in both regenerative medicine and drug screening. However, the availability of a true bioengineered vascular graft remains limited. Three-dimensional (3D) bioprinting presents a potential approach for fabricating blood vessels or vascularized tissue constructs of various architectures and sizes for transplantation and regeneration. In this review, we summarize the basic biology of different blood vessels, as well as 3D bioprinting approaches and bioink designs that have been applied to fabricate vascular and vascularized tissue constructs, with a focus on small-diameter blood vessels.